EDUCATION IN THE SPIRIT OF MILITARY PATRIOTISM AND THEIR PSYCHOLOGICAL CONCEPTS - Karimov Ravshan Abdufattoevich; Akbarov Anvar Tojimatovich; Ubaydullaev Saidakbar Saydalievich (International Engineering Journal For Research & Development, 2021)
Education in the spirit of military patriotism, love for the motherland, the psychological concept of a soldier in military service and the concept of the Constitution, the concept of Najmiddin Kubro and others.